Transformasi Peran Gender dalam Ekonomi Keluarga Transnasional di Dusun Sekunyit Kabupaten Sanggau Kalimantan Barat - Fauziah Sri Wahyuni; Iwan Ramadhan; Suriyanisa Suriyanisa (Yayasan Literasi Sains Indonesia, 2026)
The phenomenon of cross-border labor migration has shaped the Transnational Family Economy (TFE), which has impacted the transformation of gender roles within families, particularly in border areas. This study aims to describe the transformation and renegotiation of gender roles in the context of the transnational family economy in Sekunyit Hamlet, Sanggau Regency, West Kalimantan, as well as to analyze the driving factors, obstacles, and implications for family welfare. The study uses a qualitative approach with a descriptive case study design. Data were collected through in-depth interviews with transnational family members and community leaders selected purposively, then analyzed using thematic analysis. The results show that women have shifted their roles from the domestic sphere to becoming strategic economic contributors (co-breadwinners), mainly through agriculture and informal work, without completely replacing the normative role of men as the main breadwinners. This transformation is adaptive and flexible, influenced by the characteristics of the borderland economy, kinship social capital, education levels, and cross-border work experience that transfers ideological capital related to gender equality. However, these changes have not yet resulted in substantive equality because women still face a double burden due to patriarchal norms, limited access to information, and economic opportunities outside the traditional sector.